2009
DOI: 10.1103/physrevb.80.233303
|View full text |Cite
|
Sign up to set email alerts
|

GaAs(111)AandBsurfaces in hydrazine sulfide solutions: Extreme polarity dependence of surface adsorption processes

Abstract: Chemical bonds formed by hydrazine-sulfide treatment of GaAs(111) were studied by synchrotron photoemission spectroscopy. At the B surface, the top arsenic atoms are replaced by nitrogen atoms, while GaAs(111)A is covered by sulfur, also bonded to underlying gallium, despite the sulfide molar concentration being 10 3 times smaller than that of the hydrazine. This extreme dependence on surface polarity is explained by competitive adsorption processes of HS -and OH -anions and of hydrazine molecules, on Ga-adsor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
(30 reference statements)
0
7
0
Order By: Relevance
“…Surface nitridation by hydrazine sulfide solution can form a GaN monolayer at the GaAs surface. This monolayer can protect the crystal surface against oxidation over a period of months and significantly improve the GaAs optical and electrical properties. , Overall, surface nitridation is a stable and effective method for passivation of the GaAs surface. However, a comprehensive description of processes influenced by nitride passivation, in particular carrier recombination processes, is not yet available.…”
Section: Introductionmentioning
confidence: 99%
“…Surface nitridation by hydrazine sulfide solution can form a GaN monolayer at the GaAs surface. This monolayer can protect the crystal surface against oxidation over a period of months and significantly improve the GaAs optical and electrical properties. , Overall, surface nitridation is a stable and effective method for passivation of the GaAs surface. However, a comprehensive description of processes influenced by nitride passivation, in particular carrier recombination processes, is not yet available.…”
Section: Introductionmentioning
confidence: 99%
“…Surface characteristics are one of the key parameters influencing the performance and degradation of electronic and optoelectronic devices. There are numerous examples showing that distinct physical and chemical behavior can be attributed to distinct termination of semiconductor surfaces. Furthermore, occurrence of epitaxial growth frequently depends on substrate polarity . For instance, the importance of the physicochemical interactions between the two different InP faces and the chemical species present in the deposition solution were highlighted by Lincot et al, who established that CdS growth is very sensitive to the polarity of the substrate, changing from polycrystalline films obtained on the In-terminated InP(111) face to epitaxial growth on the P-terminated InP(1̅1̅1̅) face .…”
Section: Introductionmentioning
confidence: 99%
“…19,20 However, such treatment is known to produce surface microetching, which might remove a few monolayers of the GaAs material. 20,24 To avoid microetching and to prevent possible damage to the NW surface morphology, we used a low alkaline (pH ∼ 8.5) hydrazinesulfide solution in which concentration of the OH− anions is intentionally decreased by 4 orders of magnitude and microetching becomes nearly impossible. 23 Preparation of the solution included the two following stages.…”
mentioning
confidence: 99%
“…Thus, surface passivation can be provided only by a continuous nitride film with monolayer thickness. It has been demonstrated that such notably thin GaN surface films can be prepared on GaAs (100) and (111) B surfaces as a result of a rather simple wet chemical treatment in hydrazine-sulfide solution at room temperature. , The chemistry of the wet nitridation is described in detail in ref . The surface nitride monolayer forms as a result of successive chemical reactions, which begin with the removal of surface oxide under ambient alkaline conditions.…”
mentioning
confidence: 99%
See 1 more Smart Citation